Asymmetric effects of monetary policy in Brazil - Aragón, Edilean Kleber da Silva Bejarano; Portugal, Marcelo Savino (Estudos Econômicos (São Paulo), 2009)
In this paper, we check whether the effects of monetary policy actions on output in Brazil are asymmetric. Therefore, we estimate Markov-switching models that allow positive and negative shocks to affect the growth rate of output in an asymmetric fashion in expansion and recession states. In general, results show that: i) the real effects of negative monetary shocks are larger than those of positive shocks in an expansion; ii) in a recession, the real effects of positive and negative shocks are the same; iii) there is no evidence of asymmetry between the effects of countercyclical monetary policies; and iv) it is not possible to assert that the effects of a positive (or negative) shock are dependent upon the phase of the business cycle.